#### Answer

$x=\pm\sqrt{a^2+36}$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To find the solutions of the given equation, $
x^2-a^2-36=0
,$ isolate first the squared variable. Then take the square root of both sides ((Square Root Property).
$\bf{\text{Solution Details:}}$
Using the properties of equality to isolate $x$, the given equation is equivalent to
\begin{array}{l}\require{cancel}
x^2-a^2-36=0
\\\\
x^2=a^2+36
.\end{array}
Taking the square root of both sides, the equation above is equivalent to
\begin{array}{l}\require{cancel}
x=\pm\sqrt{a^2+36}
.\end{array}